Nonlinear adaptive control for multi‐machine power systems with boiler‐turbine‐generator unit. (7th February 2014) - Wan, Yong; Zhao, Jun; Dimirovski, Georgi M.
Summary This paper studies the stability of multi‐machine power systems via simultaneous design of boiler fuel flow control, turbine main steam valve control and generator excitation control for the boiler‐turbine‐generator unit. Because the whole system is coupled among generators and has multi‐parametric uncertainties, the decentralized adaptive coordinated controller design is considered and is based on the adaptive backstepping method. Moreover, in addition to the transient stability of the power angle and power oscillation, the voltage regulation is also an important property in power systems. Thus, the global control technique is used to simultaneously ensure both the transient stability and the voltage regulation. Furthermore, we improve the transient performance of power systems greatly by introducing the state‐constrained control. Simulation results show the effectiveness and advantage of the proposed controller. Copyright © 2014 John Wiley & Sons, Ltd.